A conceptual framework to promote labor force participation and career development for people with diabetes mellitus. Issue 2 (December 2019) - Strauser, David R.; Rumrill, Phillip D.; Greco, Chelsea; Strauser, D. George
Abstract: This article presents the Illinois Work and Well-Being Model as a framework that can be applied to facilitate the career development of people with diabetes mellitus. The model emphasizes the interaction of contextual and career development domains to improve participation in the areas of work, society, community, and home. This article provides a brief discussion of the potential implications of vocational rehabilitation research, service, and policy, with the overall goal of reinforcing career development as the foundation of vocational rehabilitation services for adults with diabetes mellitus and other chronic health conditions.